Interference in Macrophage Balance (M1/M2): The Mechanism of Action Responsible for the Anti-Inflammatory Effect of a Fluorophenyl-Substituted Imidazole - Julia Salvan da Rosa; Eduarda Talita Bramorski Mohr; Tainá Larissa Lubschinski; Guilherme Nicácio Vieira; Thais Andreia Rossa; Marcus Mandolesi Sá; Eduardo Monguilhott Dalmarco (Hindawi Limited, 2024)
Traditionally, the treatment of inflammatory conditions has focused on the inhibition of inflammatory mediator production; however, many conditions are refractory to this classical approach. Recently, an alternative has been presented by researchers to solve this problem: The immunomodulation of cells closely related to inflammation. Hence, macrophages, a critical key in both innate and acquired immunity, have been presented as an alternative target for the development of new medicines. In this work, we tested the fluorophenyl-imidazole for its anti-inflammatory activity and possible immunomodulatory effect on RAW 264.7 macrophages. We also evaluated the anti-inflammatory effect of the compound, and the macrophage repolarization to M2 was confirmed by the ability of the compound to reduce the M1 markers TNF-α, IL-6, MCP-1, IL-12p70, IFN-γ, and TLR4, the high levels of p65 phosphorylated, iNOS and COX-2 mRNA expression, and the fact that the compound was not able to induce the production of M1 markers when used in macrophages without lipopolysaccharide (LPS) stimulation. Moreover, fluorophenyl-imidazole had the ability to increase the M2 markers IL-4, IL-13, CD206, apoptosis and phagocytosis levels, arginase-1, and FIZZ-1 mRNA expression before LPS stimulation. Similarly, it was also able to induce the production of these same M2 markers in macrophages without being induced with LPS. These results reinforce the affirmation that the fluorophenyl-imidazole has an important anti-inflammatory effect and demonstrates that this effect is due to immunomodulatory activity, having the ability to trigger a repolarization of macrophages from M1 to M2a. These facts suggest that this molecule could be used as an alternative scaffold for the development of a new medicine to treat inflammatory conditions, where the anti-inflammatory and proregenerative properties of M2a macrophages are desired.